Immunoglobulin-free strategy to prevent HBV mother-to-child transmission in Cambodia (TA-PROHM): a single-arm, multicentre, phase 4 trial. Issue 8 (August 2022) - Segeral, Olivier; Dim, Bunnet; Durier, Christine; Nhoueng, Sovann; Chhim, Kearena; Sovann, Saren; Yom, Sophal; Vong, Chanlina; Yin, Song; Ros, Bandith; Ky, Vutha; Pech, Sothy; et al.
Summary: Background: Prevention of mother-to-child transmission (MTCT) of hepatitis B virus (HBV) is based on administration of vaccine and immunoglobulins (HBIg) to newborns at birth and maternal antiviral prophylaxis for those with an HBV-DNA viral load of at 5·3 log10 IU/mL or more. Many low-income and middle-income countries face difficulty in accessing HBIg and HBV-DNA quantification. The aim of this study was to evaluate the effectiveness of an HBIg-free strategy to prevent MTCT of HBV. Methods: TA-PROHM was a single-arm, multicentre, phase 4 trial done in five maternity units in Cambodia. Pregnant women who were positive for hepatitis B surface antigen (HBsAg), aged 18 years or older were included. Women who were HCV or HIV positive, had creatinine clearance of less than 30 mL/min, severe gravid disease, and planned to give birth outside the study sites were excluded. From Oct 4, 2017, to Jan 9, 2019, HBsAg positive pregnant women who tested positive for hepatitis B e antigen (HBeAg) with a rapid diagnostic test were eligible to receive tenofovir disoproxil fumarate. From Jan 9, 2019, women who were HBeAg negative with an alanine aminotransferase concentration of ≥40 IU/L were also eligible to receive tenofovir disoproxil fumarate. Women in the tenofovir disoproxil fumarate eligible group received 300 mg of tenofovir disoproxil fumarate orally once a day from the 24th week of gestation until 6 weeks postpartum. The primary outcome was the overall proportion of infants who were HBsAg positive at 6 months of life, confirmed by positive HBV DNA quantification. For the primary outcome, the proportion (95% CI) of infants with HBsAg at 6 months was stratified according to infant's HBIg status, duration of maternal tenofovir disoproxil fumarate treatment (>4 weeks and ≤4 weeks), and study period (before and after the change in therapeutic algorithm) and was measured in a modified intention-to-treat analysis, which excluded infants lost to follow-up or who were withdrawn before 6 months. The study is registered with ClinicalTrials.gov, NCT02937779 . Findings: From Oct 4, 2017, to Nov 27, 2020, 21 251 pregnant women were screened for HBsAg, of whom 1194 (6%) were enrolled in the study: 338 (28%) were eligible to receive tenofovir disoproxil fumarate. For the tenofovir disoproxil fumarate eligible group, four (1% [95% CI 0·34–3·20]) of 317 infants had HBV infection at 6 months; in the subgroup of 271 children who did not receive HBIg, four (1% [0·40–3·74]) had HBV infection at 6 months. In absence of HBIg, MTCT HBV transmission occurred in none (0% [0–1·61]) of 227 women who received tenofovir disoproxil fumarate for more than 4 weeks before giving birth and three (8% [1·75–22·47]) of 36 women who received tenofovir disoproxil fumarate for less than 4 weeks. In the tenofovir disoproxil fumarate ineligible group, seven (1% [0·40–2·02]) of 712 infants had HBV infection at 6 months; in the subgroup of 567 children who did not receive HBIg, six (1% [0·39–2·30]) had HBV infection at 6 months. Interpretation: An immunoglobulin-free strategy using an HBeAg rapid diagnosis test and alanine aminotransferase-based algorithm to assess eligibility for tenofovir, is effective at preventing MTCT of HBV when tenofovir was initiated at least 4 weeks before birth. Funding: French Agency for Research on AIDS and Viral Hepatitis and Emerging Infectious diseases. Translation: For the French translation of the abstract see Supplementary Materials section.